Carbon dot composite gel electrolyte and preparation method thereof
By using carbon dot composite gel electrolytes to cross-link polymerization of carbon quantum dots and DOL in lithium metal batteries, the problem of safety of liquid electrolytes and insufficient conductivity of solid electrolytes in lithium metal batteries is solved, and a lithium metal battery with high energy density and stability is achieved.
Patent Information
- Application Number
- CN202411821485.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
Liquid electrolytes in existing lithium metal batteries are prone to cause heat out of control, leading to safety problems such as fires and explosions. The brittleness and crystallization phase of solid electrolytes hinder ionic conductivity and limit their application in lithium metal batteries.
Carbon dot composite gel electrolyte is prepared by cross-linking polymerization of carbon quantum dots and DOL. By modifying insulating functional groups on the surface of carbon quantum dots, the thermal/electrochemical properties of gel electrolytes and the energy density of solid-state batteries are improved.
It improves the energy density of solid-state batteries, reduces the crystallinity of gel electrolytes, increases its ionic conductivity, alleviates the continuous decomposition of electrolytes, and improves the cycle stability and safety of the battery.
Smart Images

Figure CN119637852A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium batteries and relates to gel polymer solid electrolyte technology, and specifically to a carbon dot composite gel electrolyte and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] Lithium metal batteries are expected to become the most efficient and reliable distributed and mobile energy storage devices due to their relatively high energy density. However, lithium dendrites and flammable liquid electrolytes can easily cause thermal runaway, leading to safety issues such as fire and explosion, thus limiting their application.
[0004] Solid and quasi-solid electrolytes (including inorganic solid electrolytes, solid polymer electrolytes, gel electrolytes, etc.) are expected to perform better in terms of processability, especially safety, of lithium batteries and lithium-ion batteries, and can be used in lithium metal batteries to solve the above problems. Among them, inorganic solid electrolytes have relatively high ionic conductivity, but their brittleness limits the flexibility of their production and processing, and leads to poor interface quality between electrodes. Although solid polymer electrolytes have more advantages in processability and interface impedance, their ionic conductivity at room temperature is poor because their crystalline phase hinders ion migration. Quasi-solid gel electrolytes (i.e., gel electrolytes) are actually composites of solid polymer electrolytes and liquid electrolytes. They have higher conductivity than solid electrolytes and are safer than liquid electrolytes, so gel electrolytes are more widely used in current practical applications.
[0005] The gel electrolyte system based on poly 1,3-dioxolane (PDOL) has strong compatibility with lithium metal anode and high oxidation stability (pure PDOL and Li + / Li oxidation stability exceeds 5.0V), and it is suitable for synergistic use with many cathode materials, making it promising to solve the safety issues of lithium metal batteries. Typically, PDOL is prepared by ring-opening polymerization of 1,3-dioxolane (DOL) with initiators (such as lithium hexafluorophosphate (LiPF6), aluminum fluoride (AlF3), aluminum trifluoromethanesulfonate [Al(Otf)3], lithium difluoro(oxalate)borate (LiDFOB)). However, the prepared linear PDOL gel matrix has poor thermal / electrochemical stability, limited compatibility with electrolytes, and severe interfacial reactions, which usually result in lower energy density of the solid-state batteries assembled therefrom, thereby limiting its widespread application in lithium metal batteries. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a carbon dot composite gel electrolyte and a preparation method thereof. The present invention improves the thermal / electrochemical properties of the gel electrolyte and the energy density of the solid-state battery by modifying insulating functional groups on the surface of carbon quantum dots and cross-linking and polymerizing with DOL.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] In a first aspect, a carbon quantum dot is synthesized from citric acid and 4-aminosalicylic acid by a hydrothermal method.
[0009] In the second aspect, a carbon dot gel electrolyte, whose raw materials include 1,3-dioxolane (DOL), an organic solvent, the above-mentioned carbon quantum dots and a lithium salt, wherein the raw materials are mixed to form a precursor solution, and the precursor solution is heated and polymerized to form the carbon dot gel electrolyte; wherein the organic solvent is selected from fluoroethylene carbonate (FEC), ethylene carbonate, cyclocarbonate, dimethyl carbonate, and fluorinated vinyl methyl carbonate.
[0010] In a third aspect, a method for preparing a carbon dot gel electrolyte comprises the following steps:
[0011] Mixing DOL, an organic solvent, the carbon quantum dots and a lithium salt to prepare a precursor solution; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate and fluorinated vinyl methyl carbonate;
[0012] The precursor solution is heated to 50-65° C. for polymerization to obtain the carbon dot gel electrolyte.
[0013] In a fourth aspect, a use of the above-mentioned carbon dot gel electrolyte in the preparation of a lithium metal battery.
[0014] In a fifth aspect, a lithium metal battery includes a cathode, a lithium metal anode (referred to as lithium anode), a separator and an electrolyte, wherein the electrolyte is the above-mentioned carbon dot gel electrolyte.
[0015] Specifically, the preparation method comprises the following steps:
[0016] The cathode, lithium metal anode and separator constitute the battery structure;
[0017] Mixing DOL, an organic solvent, the carbon quantum dots and a lithium salt to prepare a precursor solution; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate and fluorinated vinyl methyl carbonate;
[0018] The precursor solution is injected into the battery structure, and after packaging, it is heated to 50-65° C. for polymerization, so that the precursor solution forms the carbon dot gel electrolyte, thereby obtaining the lithium metal battery.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention uses citric acid and 4-aminosalicylic acid to prepare carbon quantum dots through a hydrothermal method. The carbon quantum dots not only have a special main chemical structure, but also contain a large number of amino groups and hydroxyl groups on their surfaces. Studies have shown that using the carbon quantum dots for carbon dot gel electrolytes can improve the energy density of solid-state batteries.
[0021] 2. The present invention uses the carbon quantum dots prepared above to form a PDOL gel electrolyte, wherein the three-dimensional network formed by cross-linking and polymerization of the carbon quantum dots and the DOL monomers can break the regularity of the PDOL chain, so that the mobility of the PDOL chain is further improved, thereby reducing the crystallinity of the gel electrolyte and increasing its ionic conductivity. Moreover, the introduction of carbon quantum dots can promote the induction of Li + By generating smaller initial Li nuclei and constructing an ideal Li stacking to form a stable SEI (solid electrolyte interface), this design can effectively alleviate the continuous decomposition of the electrolyte and greatly increase the cycle stability of the battery.
[0022] 3. The present invention can prepare gel electrolyte by in-situ polymerization process, which is highly compatible with existing battery manufacturing process, can make electrode / electrolyte contact close, reduce interface impedance, and greatly simplify the preparation route of gel electrolyte. Compared with liquid battery, it improves thermal stability and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 This is a photo of the solidification of the carbon dot gel electrolyte prepared in Example 1 of the present invention.
[0025] Figure 2 ] are infrared spectra of the carbon dots and carbon dot gel electrolytes prepared in Example 1 and Comparative Example 1 of the present invention; wherein, (1) is the infrared spectrum of the carbon dots, (2) is the infrared spectrum of the DOL monomer, (3) is the infrared spectrum of the carbon dot gel electrolyte in Example 1, and (4) is the infrared spectrum of the carbon dot gel electrolyte in Comparative Example 1.
[0026] Figure 3 This is a DSC result diagram of the carbon dot gel electrolyte prepared in Example 1 of the present invention.
[0027] Figure 4 This is a DSC result diagram of the carbon dot gel electrolyte prepared in Comparative Example 1 of the present invention.
[0028] Figure 5 This is a graph showing the CV results of the carbon dot gel electrolyte prepared in Example 1 of the present invention.
[0029] Figure 6 This is a cycle performance diagram of a Li||LFP battery assembled with the carbon dot gel electrolyte prepared in Example 1 of the present invention at 2C;
[0030] Figure 7 is the EIS spectrum of the carbon dot gel electrolyte prepared in Example 1 of the present invention;
[0031] Figure 8 is the EIS spectrum of the gel electrolyte prepared in Comparative Example 1 of the present invention;
[0032] Fig. 9 This is a cycle performance diagram of a Li||LFP battery assembled with the gel electrolyte prepared in Comparative Example 1 of the present invention at 2C;
[0033] Fig.10 This is the EIS spectrum of the carbon dot gel electrolyte prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0036] In view of the poor thermal / electrochemical stability of PDOL gel electrolyte, its limited compatibility with electrolytes and severe interfacial reactions, which usually lead to lower energy density of solid-state batteries assembled therefrom, the present invention proposes a carbon dot composite gel electrolyte and a preparation method thereof.
[0037] A typical embodiment of the present invention provides a carbon quantum dot, which is synthesized from citric acid and 4-aminosalicylic acid by a hydrothermal method.
[0038] In some embodiments, the molar ratio of citric acid to 4-aminosalicylic acid is (1.2-1.8):1, preferably (1.4-1.6):1.
[0039] The hydrothermal method of the present invention refers to a method of heating water as a solvent under closed conditions to increase the pressure of the reaction system and perform the reaction. In some embodiments, the temperature of the hydrothermal method is 165-175° C. Specifically, the time of the hydrothermal method is 9-11 hours.
[0040] Another embodiment of the present invention provides a carbon dot gel electrolyte, wherein the raw materials include DOL, an organic solvent, the above-mentioned carbon quantum dots and a lithium salt, wherein the raw materials are mixed to form a precursor solution, and the precursor solution is heated and polymerized to form the carbon dot gel electrolyte; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate, fluorinated vinyl methyl carbonate, preferably FEC.
[0041] In some embodiments, the mass percentage of the carbon quantum dots in the precursor solution is 1.0-3.0%, preferably 1.5-2.5%.
[0042] In some embodiments, the volume ratio of DOL to organic solvent is (38-58):(40-60).
[0043] In some embodiments, the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFBO) and lithium hexafluorophosphate (LiPF6). Specifically, the concentration of the lithium salt in the precursor solution is 1.5-2.0M. The unit M in the present invention refers to mol / L. More specifically, the lithium salt is LiTFSI and LiDFBO; in the precursor solution, the concentration of LiTFSI is 1.1-1.3M, and the concentration of LiDFBO is 0.4-0.6M.
[0044] A third embodiment of the present invention provides a method for preparing a carbon dot gel electrolyte, comprising the following steps:
[0045] Mixing DOL, an organic solvent, the carbon quantum dots and a lithium salt to prepare a precursor solution; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate, fluorinated vinyl methyl carbonate, preferably FEC;
[0046] The precursor solution is heated to 50-65° C. for polymerization to obtain the carbon dot gel electrolyte.
[0047] In some embodiments, the mass percentage of the carbon quantum dots in the precursor solution is 1.0-3.0%, preferably 1.5-2.5%.
[0048] In some embodiments, the volume ratio of DOL to organic solvent is (38-58):(40-60).
[0049] In some embodiments, the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFBO) and lithium hexafluorophosphate (LiPF6). Specifically, the concentration of the lithium salt in the precursor solution is 1.5-2.0M. The unit M in the present invention refers to mol / L. More specifically, the lithium salt is LiTFSI and LiDFBO; in the precursor solution, the concentration of LiTFSI is 1.1-1.3M, and the concentration of LiDFBO is 0.4-0.6M.
[0050] In some embodiments, the polymerization reaction time is 12-48 hours.
[0051] A fourth embodiment of the present invention provides a use of the above carbon dot gel electrolyte in the preparation of a lithium metal battery.
[0052] The lithium metal battery of the present invention is generally made of a cathode, a lithium metal anode, a separator and an electrolyte, and the separator can also be removed, that is, the cathode, the lithium metal anode and the electrolyte. The battery separator can separate the conductivity between the cathode and the anode of the battery, thereby preventing short circuits and possible dangers.
[0053] In a fifth aspect, a lithium metal battery includes a cathode, a lithium metal anode (referred to as lithium anode), a separator and an electrolyte, wherein the electrolyte is the above-mentioned carbon dot gel electrolyte.
[0054] In some embodiments, the active material of the cathode is LiFePO4.
[0055] In some embodiments, the separator is glass fiber (GF). Specifically, the thickness of GF is 0.20-0.30 mm.
[0056] The carbon dot gel electrolyte of the present invention can be injected into the battery after being polymerized, or the precursor solution before polymerization can be injected into the battery and then polymerized in situ in the battery. The preparation method of in situ polymerization includes the following steps:
[0057] The cathode, lithium metal anode and separator constitute the battery structure;
[0058] Mixing DOL, an organic solvent, the carbon quantum dots and a lithium salt to prepare a precursor solution; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate, fluorinated vinyl methyl carbonate, preferably FEC;
[0059] The precursor solution is injected into the battery structure, and after packaging, it is heated to 50-65° C. for polymerization, so that the precursor solution forms the carbon dot gel electrolyte, thereby obtaining the lithium metal battery.
[0060] In-situ polymerization can make the electrode / electrolyte contact close and reduce the interfacial impedance.
[0061] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0062] Embodiment 1:
[0063] (1) Preparation of carbon quantum dots:
[0064] 2.89 g of anhydrous citric acid and 1.0 mL of 4-aminosalicylic acid were dissolved in 10 ml of ultrapure water. The solution was then transferred to an autoclave lined with polytetrafluoroethylene (Teflon), heated at 170 ° C for 10 hours, and then the autoclave was cooled to room temperature and the resulting solution was added to a beaker containing 100 mL of ethanol. The precipitate was collected by centrifugation and washed with ethanol to obtain carbon quantum dots with surface hydroxyl and amino groups.
[0065] (2) Preparation of precursor solution:
[0066] LiTFSI, LiDFOB and the carbon quantum dots obtained in step (1) are dissolved in a DOL / FEC (6:4, v / v) mixed organic solvent to obtain a precursor solution.
[0067] Wherein, in the precursor solution, the concentration of LiTFSI is 1.2 M, the concentration of LiDFOB is 0.5 M, and the mass concentration of carbon quantum dots is 2.0%.
[0068] (3) Preparation of carbon dot gel electrolyte:
[0069] The precursor solution is solidified in situ in a sealed transparent glass reagent bottle. Specifically, the precursor solution prepared in step (2) is placed at 60°C for about 24 hours to solidify in situ into a carbon dot gel electrolyte. The solidification photo of the carbon dot gel electrolyte is shown in FIG. Figure 1 As shown, the precursor is in a brown flowing state, and after polymerization, the color becomes darker and becomes a gel, which is a carbon dot gel electrolyte.
[0070] (4) Preparation of lithium metal battery (LiFePO4 / / Li battery):
[0071] (4-1) A slurry of active materials LiFePO4 (LFP), Super-p, and polyvinylidene fluoride (PVDF) (8:1:1) was uniformly dispersed and cast on aluminum foil, dried in a drying oven at 60°C for 3 h, and then dried in a vacuum oven at 120°C for 12 h to prepare a LiFePO4 cathode. The mass loading of the active material in the cathode was about 1.8 mg cm -2 .
[0072] (4-2) In an argon-filled glove box, the cathode, lithium anode and glass fiber GF / A separator (thickness 0.26 mm) were assembled into a CR2025 button cell; after injecting 80 μL of the precursor solution obtained in step (2), the battery was heated at 60° C. for 24 hours to obtain a lithium metal battery.
[0073] The carbon dots and carbon dot gel electrolyte prepared in this example were observed and tested as follows:
[0074] Fourier transform infrared spectroscopy (FTIR): Attenuated total reflectance mode (ATR-FTIR) is used to analyze the chemical structure. The measured spectrum range is recorded as 500-4000cm -1 , scanned 128 times.
[0075] Differential Scanning Calorimeter Test (DSC): Use the DSC25 differential scanning calorimeter of TA Company in the United States in the temperature range of -20℃~60℃, in air atmosphere, and the temperature change rate is 10℃min -1 Conduct a test.
[0076] Electrochemical cycle test: Using the Land test system of Wuhan Landian Electronics Co., Ltd., a 2C cycle test was performed on the LiFePO4 / / Li battery prepared in step (4) at a temperature of 30°C and a charge and discharge voltage range of 2.5-4.1V.
[0077] Cyclic voltammetry test (CV): Using Shanghai Chenhua Company's CHI660E electrochemical workstation, the main charge and discharge voltage range of the LiFePO4||Li battery is 2.5-4.1 V, and the test potential range is 2.5-4.1 V. The LiFePO4 / / Li battery prepared in step (4) was subjected to CV test at a scan rate of 0.1 mVs-1.
[0078] The infrared spectra of the carbon dots and carbon dot gel electrolyte prepared in this example are as follows: Figure 2 As shown in the curve of carbon dot gel electrolyte, the characteristic peak of cyclic ether vibration in DOL disappears (1082cm -1 , 914cm -1 ), while the vibration characteristic peak of the long chain ether in PDOL (841cm -1) appeared, indicating that the target product PDOL was generated. At the same time, compared with PDOL, the characteristic peaks of carbon dot gel electrolyte COC shifted, which was caused by the hydrogen bonding interaction between carbon dots and PDOL molecules.
[0079] The DSC results of the carbon dot gel electrolyte prepared in this example are as follows: Figure 3 As shown, the glass transition temperature (T g ) is 50.2℃, indicating that the CDPE electrolyte composited with carbon dots has higher segment mobility, which helps the internal Li + transmission; and there is no obvious melting endothermic peak between 30-60℃, indicating that its crystallinity is very low.
[0080] The CV results of the LiFePO4 / / Li battery (Li||LFP battery) based on carbon dot gel electrolyte prepared in this example are as follows: Figure 5 As shown. The potential difference between the redox peaks represents the polarization voltage. The polarization voltage of the Li||LFP battery is 0.21V. A small polarization voltage helps the battery to work stably at a large current. In addition, the cyclic voltammetry (CV) curve of the carbon dot gel electrolyte overlaps well with the anodic peak of 3.55V and the cathodic peak of 3.35V. This is a typical electrochemical redox peak of LiFePO4, indicating that only redox conversion occurs at the anode and there is no side reaction of LiFePO4.
[0081] The cycling performance of the Li||LFP battery assembled with the carbon dot gel electrolyte prepared in this embodiment at a 2C rate is shown in the figure below. Figure 6 As shown. Li||LFP battery achieved 138.5mAhg -1 It has a high capacity and an ultra-long life of 2000 cycles, and an excellent reversible cycle capacity retention rate of 92% at a high rate of 2C.
[0082] Figure 7 is the EIS spectrum of the carbon dot gel electrolyte prepared in Example 1. The ionic conductivity was found to be 3.20 mS / cm.
[0083] Example 2
[0084] This embodiment is the same as embodiment 1, except that FEC is replaced by ethylene carbonate.
[0085] Example 3
[0086] This embodiment is the same as embodiment 1, except that FEC is replaced by cyclic carbonate.
[0087] Example 4
[0088] This embodiment is the same as embodiment 1, except that FEC is replaced by dimethyl carbonate.
[0089] Example 5
[0090] This embodiment is the same as embodiment 1, except that FEC is replaced by fluorinated vinyl methyl carbonate.
[0091] Comparative Example 1
[0092] The same as Example 1, except that no carbon quantum dots are added to the precursor solution.
[0093] The DSC results of the carbon dot gel electrolyte prepared in this comparative example are as follows: Figure 4 As shown. T in Example 1 g The T of Example 1 is 50.2°C. g (-56.3℃), which indicates that the carbon dot gel electrolyte formed after composite with carbon dots has higher segment mobility and helps the internal Li + and compared with Example 1, Comparative Example 1 has a more obvious melting endothermic peak between 30-60°C, indicating that it has a higher degree of crystallinity, while the carbon dot gel electrolyte has more free segments.
[0094] The EIS spectrum of the gel electrolyte prepared in this comparative example is as follows: Figure 8 As shown. Through the formula The ionic conductivity was found to be 1.69 mS / cm, which is obviously lower than that in Example 1, proving that carbon dots improve electrolyte performance.
[0095] The cycling performance of the Li||LFP battery assembled with the gel electrolyte prepared in this comparative example at a 2C rate is shown in the figure below. Fig. 9 As shown, it is obviously lower than the battery performance of carbon dot gel electrolyte.
[0096] Comparative Example 2
[0097] Same as Example 1, except that graphene quantum dots are used. The preparation method of graphene quantum dots is as follows: 5.0g of graphite is added to a mixture of 240mL of 98% sulfuric acid and 80mL of 68% nitric acid, ultrasonically treated for 4h, stirred at 120°C for 24h, cooled to room temperature, diluted the reaction system with deionized water, and neutralized with potassium carbonate (adjusting the pH to 5.5). After filtration, a brown aqueous solution is obtained by filtering with a 0.2μm polytetrafluoroethylene membrane. The aqueous solution is dialyzed with deionized water in a dialysis bag (2000 Daltons) for one week to obtain 2.38g of graphene quantum dots.
[0098] Fig.10 is the EIS spectrum of the carbon dot gel electrolyte prepared in Comparative Example 2. The ionic conductivity was found to be 1.77 mS / cm, which is obviously lower than that in Example 1. This may be because the graphene quantum dots have a large lateral size and aggregate, resulting in phase separation or uneven distribution within the electrolyte, which hinders the ion transport pathway and reduces performance.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbon quantum dot, characterized in that: It is synthesized from citric acid and 4-aminosalicylic acid by a hydrothermal method.
2. The carbon quantum dots according to claim 1, characterized in that: The molar ratio of citric acid to 4-aminosalicylic acid is (1.2-1.8):1, preferably (1.4-1.6):1; Alternatively, the temperature of the hydrothermal method is 165-175° C.; preferably, the time of the hydrothermal method is 9-11 hours.
3. A carbon dot gel electrolyte, characterized in that: Its raw materials include DOL, organic solvent, carbon quantum dots according to claim 1 or 2, and lithium salt. The raw materials are used to mix to form a precursor solution, and the precursor solution is used to heat and polymerize into the carbon dot gel electrolyte; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate, fluorinated vinyl methyl carbonate, preferably FEC.
4. The carbon dot gel electrolyte according to claim 3, characterized in that: The mass percentage of the carbon quantum dots in the precursor solution is 1.0-3.0%, preferably 1.5-2.5%; Or, the volume ratio of DOL to the organic solvent is (38-58):(40-60); Or, the lithium salt is one or more of LiTFSI, LiDFBO and LiPF6; preferably, the concentration of the lithium salt in the precursor solution is 1.5-2.0M; preferably, the lithium salt is LiTFSI and LiDFBO; In the precursor solution, the concentration of LiTFSI is 1.1-1.3M, and the concentration of LiDFBO is 0.4-0.6M.
5. A method for preparing a carbon dot gel electrolyte, characterized in that: The steps include: DOL, an organic solvent, the carbon quantum dots according to claim 1 or 2, and a lithium salt are mixed to prepare a precursor solution; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate, fluorinated vinyl methyl carbonate, preferably FEC; The precursor solution is heated to 50-65° C. for polymerization to obtain the carbon dot gel electrolyte.
6. The method for preparing the carbon dot gel electrolyte according to claim 5, characterized in that: The mass percentage of the carbon quantum dots in the precursor solution is 1.0-3.0%, preferably 1.5-2.5%; Alternatively, the volume ratio of DOL to the organic solvent is (38-58):(40-60). Or, the lithium salt is one or more of LiTFSI, LiDFBO and LiPF6; preferably, the concentration of the lithium salt in the precursor solution is 1.5-2.0M; preferably, the lithium salt is LiTFSI and LiDFBO; In the precursor solution, the concentration of LiTFSI is 1.1-1.3M, and the concentration of LiDFBO is 0.4-0.6M.
7. The method for preparing the carbon dot gel electrolyte according to claim 5, characterized in that: The polymerization reaction time is 12-48 hours.
8. Use of the carbon dot gel electrolyte according to claim 3 or 4 or the carbon dot gel electrolyte obtained by the preparation method according to any one of claims 5 to 7 in preparing a lithium metal battery.
9. A lithium metal battery, characterized in that: The invention comprises a cathode, a lithium metal anode, a separator and an electrolyte, wherein the electrolyte is the carbon dot gel electrolyte according to claim 3 or 4 or the carbon dot gel electrolyte obtained by the preparation method according to any one of claims 5-7.
10. The lithium metal battery according to claim 9, characterized in that: The active material of the cathode is LiFePO4; Or, the diaphragm is GF; Or, the preparation method comprises the following steps: The cathode, lithium metal anode and separator constitute the battery structure; Mixing DOL, an organic solvent, the carbon quantum dots and a lithium salt to prepare a precursor solution; wherein the organic solvent is selected from FEC, ethylene carbonate, cyclic carbonate, dimethyl carbonate, fluorinated vinyl methyl carbonate, preferably FEC; The precursor solution is injected into the battery structure, and after packaging, it is heated to 50-65° C. for polymerization, so that the precursor solution forms the carbon dot gel electrolyte, thereby obtaining the lithium metal battery.